ASAS KEPASTIAN HUKUM DAN ASAS KEBEBASAN BERKONTRAK SEBAGAI PERTIMBANGAN UTAMA DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH (Kajian Yuridis Putusan MK Nomor 93/PUU-X/2012) - Edi Hudiata (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Since the verdict of the Constitutional Court (MK) Number 93/PUU-X/2012 pronounced on Thursday, August 29, 2013, concerning the judicial review of Law No. 21 of 2008 on Islamic Banking, it is no longer dualism dispute resolution. The verdict as well as strengthen the jurisdiction of Religious Court to resolve Islamic banking disputes. In consideration of the judges, judges agreed stating that Article 55 paragraph (2) and (3) of Law No. 21 of 2008 which is an ideal norm, contains no constitutional problems. The problem is the explanation of the constitutional article 55 paragraph (2) of the Act. The emergence of the Constitutional Court verdict No. 93/PUU-X/2012 which substantially states that the explanation of Article 55 paragraph (2) of Law No. 21 of 2008 does not have binding force, basically does not violate the principle of freedom of contract which is common in contract law. The parties are allowed to make a dispute resolution agreement out of religious court based on provisions as Act No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. Keywords: dispute resolution, legal certainty and the principle of freedom of contract